Liquid crystal-based actuators - Gruzdenko, Alexandra; Dierking, Ingo (Frontiers in Soft Matter, 2022)
Liquid crystal polymer networks (LCNs) have a great potential in soft actuator technologies. In contrast to other materials, LCNs offer a wide range of external stimuli which can trigger their actuation. These are for example based on changes of temperature, photo-induced or via the application of electric or magnetic fields. We here discuss the main LCN actuation mechanisms and classify them into several groups based on the used stimulus. Specific recent examples are provided for liquid crystal actuators and several general applications of such materials in connection to actuation mechanisms are exemplary outlined.